Vegetation and Selected Environmental Factors of Bukit Charas Limestone - Soh, Wuu Kuang (2002)
The Limestone flora of Peninsular Malaysia is exceptionally rich in diversity and endemism but is under extreme threat. Moreover, the ecology of limestone plants is little understood. Bukit Charas stands out as one of the last sanctuaries for the flora of the Panching Limestone Formation. Therefore a floristic and ecological study were undertaken to document and conserve the hill. The flora in this study stood at 249 species in 175 genera and 82 families. The largest family is the Euphorbiaceae (19) followed by the Rubiaceae (18), Araceae (13), Annonaceae (10) and Lauraceae (7). Six rare species; (Suregada multiflora var lamellata, Ardisia sujJrutieosa, Teetaria eherasiea, Emarhendia bettiana, Monophyl/aea hendersonii and Polyalthia sp.) are recognised from Bukit Charas. Cluster analysis has identified four types of vegetation groups at the base of the hill (BASE), at the slope of the hill (SLOPE), at the talus slope (TALUS) and at the cave (CAVE). Plants, characteristic to the limestone habitat are found in the TALUS and CAVE groups. Twelve environmental variables have been used for ordination. Unrotated principal component analysis has reduced these variables to two components, i.e. calcium and magnesium; and kalium and carbonate. Two primary environmental gradients were identified with the Varimax-rotated principal component .analysis of environmental data: topographic situation and soil fertility. The TALUS and CAVE groups were significantly associated with high level of soil exchangeable calcium and magnesium. The TALUS group is also associated with high organic matter and the CAVE group with high carbonate content. The results of the species and quadrat ordination of the detrended correspondence analysis were similar to the principal component analysis. Three hypotheses are proposed: Firstly, the plant endemism in limestone habitat is greatly driven by edaphic factor and not by the need to avoid competition. Secondly, the high level of exchangeable calcium and magnesium, and high soil pH in the limestone soil act as important limiting factors for limestone endemics. These conditions are important requirements for limestone habitats. Thirdly, there exist limiting factors within a limestone habitat that create a niche partition among the limestone endemic species. The current threat to Bukit Charas flora is agricultural activities at the surrounding base of the hill. A buffer zone that stretched 50 m from the forest margin is proposed as a strategy to conserve Bukit Charas. Future study should be expanded to other hills for comparison and green house experiment should be undertaken to test the hypotheses.